Caregiver Perceptions of the Transition From Paediatric Intensive to Acute Care - Maia D. Regan; Briana P. Keller; Emily Boulos; Kristina Betters; Jessika C. Boles (Nursing in Critical Care, 2026)
ABSTRACT Background Transfer from the intensive care unit to an acute care unit is reportedly a stressful time for adult patients and their families. However, little has been done to understand these transition experiences and needs in paediatric patients and their parents/caregivers. Aim To describe parent/caregiver perceptions of their child's transition from the paediatric general or cardiac intensive care unit to an acute care unit. Study Design Using a descriptive electronic survey‐based design, parents/caregivers reported their perceptions of the quality of their child's transition from a paediatric intensive care unit to an acute care unit in a United States hospital, as well as their perceptions about the care received in each location. Responses were analysed using sign tests, Spearman's rank correlations and other non‐parametric tests. Results A total of 87 parents/caregivers participated. Participants reported significantly more positive perceptions of the quality of intensive care their child received compared to acute care experiences across all response domains ( z = −0.3921, p < 0.001); this effect held significance even for those with prior paediatric intensive care admissions ( z = −2.1971, p = 0.028). Those who reported receiving adequate preparation and information regarding transfer across units were more likely to report more positive perceptions of overall care quality ( r (82) = 0.817, p < 0.001). Conclusions Transferring from the paediatric intensive care unit is a challenging event for paediatric patients and families. With intentional, effective communication and preparation, healthcare providers can empower caregivers as their child's condition improves. Relevance to Clinical Practice Families who feel more prepared for transition to acute care are more satisfied with their overall care experience and report that their needs are better met. Intensive care and acute care providers should collaborate on transfer planning initiatives that ensure families are informed, prepared for and supported during transfer between units.